An Assessment of the U.S. Environmental Protection Agency's National Environmental Performance Track Program - Hassell, Scott (RAND Corporation, 2010)
This report addresses the conceptual basis, design, and implementation of the National Environmental Performance Track program. The voluntary program sought to encourage facilities to improve their environmental performance and provide a more collaborative relationship between facilities and regulators. While the program had mixed success, EPA should continue to seek out new approaches to complement and enhance traditional regulatory approaches.